Wide-field calcium imaging of cortex-wide activity in awake, head-fixed mice - Chi Ren (Elsevier, 2021)
Summary: Characterizing cortex-wide neural activity is essential for understanding large-scale interactions among distributed cortical regions. Here, we describe a protocol using wide-field calcium imaging to monitor the cortex-wide activity in awake, head-fixed mice. This approach provides sufficient signal-to-noise ratio and spatiotemporal resolution to capture large-scale neural activity in behaving mice on a moment-by-moment basis. The use of genetically encoded calcium indicators allows longitudinal imaging over months and can achieve cell-type specificity. We also describe a pipeline to process the imaging data.For complete details on the use and execution of this protocol, please refer to Makino et al. (2017) and Liu et al. (2021).